Emotional design for children's food packaging / Wang Haiying and Muhamad Abdul Aziz Ab. Gani - Haiying, Wang; Ab. Gani, Muhamad Abdul Aziz (Universiti Teknologi MARA, Perak, 2022)
Children's food packaging is the most diverse and colorful of packaging designs. The difficulty lies in reflecting the characteristics of children's food, but also making children associate with it through the packaging, so that the packaging design can bring them more fun. Children as a consumer group have their own uniqueness. Children's physiological and psychological development different from adults in terms of food concerns. Some designers do not pay enough attention to the cognitive psychology of children, resulting in many children's food packaging lacking fun and not fully reflecting emotional care. This study introduces the theory of emotional design into the children's food packaging design, combining the knowledge of five senses design and other related fields to establish the emotional relationship between children and children's food packaging. Through literature review and data survey analysis, scientific and objective design principles are established. A questionnaire survey was used to understand children's preferences for packaging. 300 primary school students aged 7-12 were studied, and the results showed that food packaging that meets children's emotional needs can stimulate their desire to buy.